Upaya Meningkatkan Hasil dan Minat Belajar Materi Besaran dan Satuan Melalui Model Discovery Learning pada Fase E SMA Darunnajah Sumenep - Sunariatus Solehah; Herman Jufri Andi; Luaini Luaini; Syaiful Bahri; Moh Syamsul (Universitas Palan, 2024)
The purpose of this research is to describe the results and learning interest of students by applying the Discovery Learning model. This shows an improvement in student learning outcomes with the application of Discovery Learning. This improvement is because students have started to understand the material that has been learned using the Discovery Learning model in phase E. while the data analysis used descriptive methods with the success of student learning activities. And the results of the data analysis showed that the improvement in learning outcomes for class X students at SMAS Islam Darunnajah Sumenep with Discovery Learning on the topic of quantities and units increased from 55% in cycle 1 to 85% in cycle 2, with an overall improvement of 30% between the two cycles. The improvement in learning outcomes indicates that the implemented Discovery Learning can be enjoyable and make students interested and engaged in the learning process.